War crimes law, politics, and armed conflict in the modern world - Remy, Steven P. 1967- (Seminar Studies, 2023)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- List of figures -- Chronology -- Who's who -- Acknowledgments -- Introduction -- Part I War crimes and the laws of war in the era of global war (1863-1945) -- 1 The 19th century in the United States and Europe -- 2 Colonial wars -- 3 Between the Hague and Nuremberg -- 4 The Nuremberg and Tokyo tribunals -- 5 National trials in Europe and Asia -- Part II The world of war crimes and international law after World War II -- 6 War crimes and international law in the Cold War and the era of decolonization -- 7 From International Criminal Tribunals to the International Criminal Court -- 8 Women and war crimes -- 9 Future war: private military companies, drones, cyberwar, and ecocide -- 10 Memory, transitional justice, and the investigative turn -- Part III Documents -- Glossary -- Guide to further reading -- Bibliography -- Index.